PENINGKATAN KONSENTRASI DAN HASIL BELAJAR BANGUN DATAR BERBASIS ETNOMATEMATIKA - Setiani, Rizka; Sumarah, Ignatia Esti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This research is motivated by initial findings in class III of SDK Sang Timur Yogyakarta which showed that there were students with low learning concentration and Mathematics learning outcomes of flat shape material that had not reached the Learning Objective Completion Criteria (KKTP) of 70. The focus of this research problem is how to improve students' concentration and Mathematics learning outcomes. To overcome this problem, Classroom Action Research (CAR) was conducted consisting of two cycles by implementing ethnomathematics-based learning media. The subjects of the study were 20 class III students, consisting of 10 males and 10 females. Data collection was carried out through interviews, observations of 6 concentration indicators, documentation studies, and learning outcome tests. The results of the study showed a significant increase. The percentage of